Once An Arafat Man - Saada, Tass; Nang Chan Yeema (Carol Stream, Illinois, United States Tyndale House Publishers, Inc., 2002)
Once an Arafat man: the true story of how a PLO sniper found a new life/ Tass Saada, with Dean Merrill.
Keywords: Young Adult